Limited Cutaneous Scleroderma - Putu Gde Hari Wangsa; Prima Sanjiwani Saraswati Sudarsa; Made Hermina Laksmi (Intisari Sains Medis, 2021)
Introduction: Scleroderma is a rare autoimmune disease of connective tissue characterized by extensive fibrosis, inflammation, and vasculopathy. It classified as limited cutaneous and diffuse based on the degree of skin involvement. The management is still a challenge since it has a high morbidity and mortality rate. This case report aims to understand scleroderma and provide appropriate treatment that can improve the patient's prognosis.Case report: A 55-year-old female came with complaints of stiff skin on the forearms, lower legs and face since approximately eight months ago, initially on the right and left forearms, then to face, right and left lower legs. On physical examination, there was sclerosis of the skin on the face, forearms and lower legs, and salt and pepper appearance with Rodnan score were 26. The result from histopathological examination were sceleroderma. The patient was diagnosed with limited cutaneous scleroderma. The management consisted of methotrexate, folic acid, sulpha ferrous, vitamins B1, B6, B12 intraorally and 10% urea cream topically. She also was informed to practice moving the hands and fingers slowly.Conclusion: The diagnosis of limited cutaneous scleroderma is based on history, physical examination and investigations. It is still a life-threatening disease, however multidisciplinary management with early detection and treatment of complications can improve the prognosis.